Effect of Different Substrates on Nutritional Composition of Shiitake Mushroom (Lentinula edodes) - , Shazia Paswal; , Sardar Singh Kakraliya; , Vinod Fogawat (Archives of Current Research International, 2024)
Lentinula edodes (Berk.) Peglar, the shiitake mushroom, is worldwide one of the most widely cultivated mushrooms. The cultivation of edible mushrooms is a biotechnological process that uses various residues to produce food of high nutritional value. Two strains of Lentinula edodes (DMR-356 and DMR-35) were cultivated on basal substrates wheat straw and poplar sawdust alone and in combination with supplements (Wheat bran, Rice bran and Maize Meal). The fruit body of shiitake mushroom was analyzed for crude protein, crude fiber, Moisture content, crude fat, total ash and total carbohydrates. DMR-356 strain proved best for high nutritional value crude protein (22.44%), crude fat (3.97%), crude fibers (7.69%), total ash (7.75%), and total carbohydrates (63.50%) with substrates wheat straw + wheat bran. The least effective substrate was sawdust alone.